Expression of SIRT1 and DBC1 in Gastric Adenocarcinoma - Kang, Youngran (The Korean Society of Pathologists and The Korean Society for Cytopathology, 2012)
BACKGROUND: Sirtuin 1 (SIRT1) and deleted in breast cancer 1 (DBC1) are known as tumor suppressor or promoter genes. This may be due to their diverse functions and interaction with other proteins. Gastric adenocarcinoma is one of the most common malignancies, but little is known about its carcinogenesis. Therefore, we investigated the association of immunohistochemical expression of SIRT1, DBC1, p53, and β-catenin and their variable clinicopathological characteristics. METHODS: We obtained samples from 452 patients who underwent gastrectomy. Tissue microarray blocks were constructed and immonohistochemical staining was performed. RESULTS: Expression of DBC1 and SIRT1 was associated with lower histologic grade, intestinal type of Lauren classification, and lower pT (p<0.001) and pN stage (DBC1, p=0.002; SIRT1, p<0.001). Association between absence of lymphatic invasion, and SIRT1 (p=0.001) and DBC1 (p=0.004) was observed. Cytoplasmic β-catenin expression was associated with lower histologic grade, pT, pN, tumor-node-metastasis (TNM) stage, DBC1 (p<0.001), and SIRT1 (p=0.001). Expression of SIRT1 and DBC1 was not associated with p53 (p=0.063 and p=0.060). DBC1 was an independent good prognostic factor in multivariate analysis (p=0.012). CONCLUSIONS: SIRC1 and DBC1 can be considered to be good prognostic factors in gastric adenocarcinoma.